Tracheal bronchus and empyema in a pediatric patient: a rare and unreported association - Mohmmed A. Mohmmedahmed; Syed Essa Iraj; Hassan ALBahrani; Khalid Bait Jamil; Bashir A. Yousef; Omar Ibrahim (The Egyptian Journal of Bronchology)
Abstract Tracheal bronchus (TB), also known as pig bronchus, is a rare tracheobronchial congenital anomaly that occurs when the right upper lobe bronchus originates from the trachea rather than the carina. It can be symptomatic with respiratory symptoms such as persistent cough, wheezing, stridor, respiratory distress, and recurrent pneumonia, or it may be found incidentally during bronchoscopy or chest computed tomography (CT) in asymptomatic patients. The estimated prevalence is around 1–3% worldwide. We report a unique case of a 7-year-old girl with a TB who developed empyema, a previously undocumented association in pediatric literature. This report discusses the clinical presentation, management, and relevant literature, emphasizing the importance of considering TB although it is rare as a differential diagnosis of children with recurrent or persistent respiratory problems.